2021
DOI: 10.1101/2021.05.13.21257161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Occupation, Work-Related Contact, and SARS-CoV-2 Anti-Nucleocapsid Serological Status: Findings from the Virus Watch prospective cohort study

Abstract: Background: Workers differ in their risk of acquiring SARS-CoV-2 infection according to their occupation; however, few studies have been able to control for multiple confounders or investigate the work-related factors that drive differences in occupational risk. Using data from the Virus Watch community cohort study in England and Wales, we set out to estimate the total effect of occupation on SARS-CoV-2 serological status, whether this is mediated by frequency of close contact within the workplace, and how ex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
(40 reference statements)
2
11
0
Order By: Relevance
“…The results showed indeed that higher-risk scores attributed by the COVID-19-JEM were associated with a higher incidence of self-reported COVID-19, except for the dimensions on precarious work. This observed association is in line with other studies investigating associations between topics similar to the transmission and mitigation factors of the COVID-19-JEM and COVID-19 or other respiratory diseases ( Jefferson et al , 2008 ; Kampf et al , 2020 ; Vokó and Pitter, 2020 ; Backer et al , 2021 ; Beale et al , 2022 ; Li and Tang, 2021 ). These findings indicate that the COVID-19-JEM is a useful tool for assessing the risk of having had COVID-19 when data on exposure at individual level are lacking.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results showed indeed that higher-risk scores attributed by the COVID-19-JEM were associated with a higher incidence of self-reported COVID-19, except for the dimensions on precarious work. This observed association is in line with other studies investigating associations between topics similar to the transmission and mitigation factors of the COVID-19-JEM and COVID-19 or other respiratory diseases ( Jefferson et al , 2008 ; Kampf et al , 2020 ; Vokó and Pitter, 2020 ; Backer et al , 2021 ; Beale et al , 2022 ; Li and Tang, 2021 ). These findings indicate that the COVID-19-JEM is a useful tool for assessing the risk of having had COVID-19 when data on exposure at individual level are lacking.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we need to be aware that only one third of the infected study population thought they were infected at the worksite. Even though this is a substantial proportion which is in line with what others have reported ( Lan et al , 2020 ; Beale et al , 2022 ), it also means that it is not the only key setting of being infected with SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Several studies have found increased risks of infection and mortality from COVID-19 amongst healthcare workers (5)(6)(7)(8) and those working in public facing transport occupations when compared to non-essential or other workers. Other studies have not found an increased risk (9) or suggest it varies by type of worker and/or stage of the pandemic (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%